2019
DOI: 10.29252/ijn.32.118.86
|View full text |Cite
|
Sign up to set email alerts
|

Self-care Agency and Its Influential Factors in Hemodialysis Patients

Abstract: Background & Aims: Hemodialysis is currently a common treatment for chronic renal disease, which is associated with numerous limitations in the physical, mental and even social function of the patients. As such, self-care activities could significantly help hemodialysis patients to adapt to the course of their disease. The present study aimed to determine self-care agency and its influential factors in hemodialysis patients. Materials & Methods: This cross-sectional was conducted on the patients referring to R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…These findings are in line with previous studies and indicate that self-care of HD patients decrease over the time. 6 , 2 , 42 However Unsar et al, found no significant relationship between age and self-care in HD patients. 13 It seems that with the age increasing, physical problems and care requisites will increase in HD patients as they have lower energy for self-care than the younger patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are in line with previous studies and indicate that self-care of HD patients decrease over the time. 6 , 2 , 42 However Unsar et al, found no significant relationship between age and self-care in HD patients. 13 It seems that with the age increasing, physical problems and care requisites will increase in HD patients as they have lower energy for self-care than the younger patients.…”
Section: Discussionmentioning
confidence: 97%
“… 1 The most common treatment that alleviates the symptoms and rescues the patients’ life is HD. 2 The prevalence of CKD is increasing in the world for many reasons. 3 An annual growth of 5-6 percent in the CKD compared to population growth has been a challenge in all countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Better outcomes from self-management and enhanced mental health are associated with higher patient self-efficacy [56]. Furthermore, educating and supporting patients toward self-centeredness can enhance disease management and decrease healthcare expenses [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy is the belief in a person's ability to successfully achieve something and is very important for managing chronic diseases like CKD. 12 Good self-efficacy enables hemodialysis patients to be more actively involved in self-care management. It also improves the health-related quality of life, level of cooperation with the family and paramedics, communication, and medication adherence.…”
Section: Introductionmentioning
confidence: 99%